The Impact of Accounting Regulation Implementation on MSME Performance - Mutiara Maimunah; Desy Lesmana; Delfi Panjaitan; Antonius Singgih Setiawan (Jurnal Akuntansi, 2026)
This study analyzes the impact of accounting regulation implementation on MSME performance, with regulation implementation as the independent variable and MSME performance as the dependent variable. The research focuses on whether the level of compliance and understanding of accounting regulations improves business performance. A quantitative approach was used with a survey method, collecting data through structured questionnaires from 88 respondents. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results show that the implementation of accounting regulations has a positive and significant effect on MSME performance. This indicates that better compliance and application of accounting standards enhance financial management quality and support improved business outcomes.